Characterization of Friction Properties During Machining of Various Stainless Steels - Pierre NAISSON; Joel RECH; Henri PARIS (Engineering Transactions, 2013)
Many issues in machining are related to interface characteristics, such as the friction coefficient, adhesive layer, or heat transfer coefficient. A specially designed tribometer is used to quantify these contact parameters in the case of four stainless steels (three austenite grade with controlled composition and an austenito-ferritic one). The sensitivity to sliding velocity and coatings is investigated. It is highlighted that the contact pressure effect is limited compared with the influence of sliding speed. Moreover, tool damage can also be explained by local phenomena exhibited by the tribometer, such as adhesion layer or thermal aspects, hich are critical in case of stainless steels.